The Logic of Modern Constitutional Legitimacy: From Magna Carta to the Bill of Rights (1215–1689) (MINDEN Journal of History and Archaeology, 2026)
Spanning the five centuries between Magna Carta (1215) and the Bill of Rights (1689), this study re-examines the making of England’s constitutional order and argues that legitimacy was not the product of seamless progress or episodic rupture, but of a continual re-appropriation of inherited forms. It identifies three overlapping paradigms—feudal contract, parliamentary sovereignty and rights universalisation—through which successive generations re-articulated political obligation while maintaining a rhetoric of continuity. Medieval jurists first used the language of mutual obligation to circumscribe royal prerogative; Tudor and early-Stuart polemicists then adapted that vocabulary to elevate Parliament; by the late seventeenth century, appeals to the “ancient constitution” fused with natural-law theory, translating corporate privileges into individual rights. The analysis draws on royal charters, plea rolls, parliamentary journals and printed pamphlets, integrating legal exegesis with social-historical method to show how selective memory served as a legitimising resource. By uncovering the bricolage that transformed a feudal pact into a constitutional monarchy, the article challenges linear Whig narratives and contributes to comparative debates on state formation, the politics of tradition and the contingent evolution of constitutional norms in early modern Europe.Keywords: Magna Carta; Bill of Rights; England’s constitutional; natural-law theory; Whig